2002
DOI: 10.1186/1471-2091-3-14
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of HIV-1 Tat expressing cells: a close interplay between proliferative and differentiation signals

Abstract: Background: Expression profiling holds great promise for rapid host genome functional analysis. It is plausible that host expression profiling in an infection could serve as a universal phenotype in virally infected cells. Here, we describe the effect of one of the most critical viral activators, Tat, in HIV-1 infected and Tat expressing cells. We utilized microarray analysis from uninfected, latently HIV-1 infected cells, as well as cells that express Tat, to decipher some of the cellular changes associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(12 citation statements)
references
References 105 publications
1
11
0
Order By: Relevance
“…The third group of gene sets that is usually modulate by virus is the host cell transcription apparatus [31]. By providing direct gene pattern, our results confirmed that this strategy was also exploited both in the HIV mono- and HCV/HIV co-infected individuals.…”
Section: Discussionsupporting
confidence: 72%
“…The third group of gene sets that is usually modulate by virus is the host cell transcription apparatus [31]. By providing direct gene pattern, our results confirmed that this strategy was also exploited both in the HIV mono- and HCV/HIV co-infected individuals.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, we took advantage of this marker to perform, for the first time, comparative genomic profiling of primary latently infected resting memory CD4 ϩ T cells versus their uninfected counterparts sorted from the same culture. Previous studies were carried out with latently infected cell lines (55)(56)(57), but no studies using primary CD4 ϩ T cells have been reported. Krishnan et al showed altered expression levels of genes encoding components of the proteasome, histone deacetylases, and transcription factors in the chronically infected cell lines ACH-2, J1.1, and U1 compared to the parental uninfected cell lines A3.01, Jurkat, and U937 (56).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our microarray study indicated that in latently infected cells, gene programs were modulated in a way that is consistent with cell quiescence, cell survival, transcription silencing, and evasion of the immune system. Since HIV-1 proteins have a profound effect on many host cell functions that are relevant to its life cycle (55,58,(62)(63)(64)(65)(66)(67)(68)(69), it is conceivable that they might also affect cell functions relevant to latency. On the other hand, it is possible to speculate that a subset of CD4 ϩ T cells with a gene expression profile similar to the one emerging from our microarray analysis already preexists in peripheral blood of healthy individuals, so that upon HIV-1 infection, it provides an ideal environment for the establishment of latency.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in the HIV-1 life cycle, Tat has the ability to influence a cell's phenotype by modulating the expression of cellular genes [6,7]. The protein has been found to stimulate the expression of immuno-regulatory cytokines, including the production of IL-6, the dysregulation of which is implicated in the pathogenesis of several AIDS-associated pathologies such as psoriasis, B cell lymphoma and Kaposi's sarcoma [8].…”
Section: Introductionmentioning
confidence: 98%